Implementation of the Numbered Heads Together Model Based on Problem Based Learning on Students’ Interest and Understanding of Mathematical Concepts - Izza, Anisa Qarinatul; Mubarokah, Khofifah Indah; Pratama, Loviga Denny (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Mathematics is often perceived by students as a difficult and uninteresting subject, highlighting the need for a learning model that not only fosters interest but also strengthens conceptual understanding. Previous studies have shown a gap in the optimal integration of the cooperative Numbered Heads Together (NHT) model with the Problem Based Learning (PBL) approach, even though both have the potential to promote active engagement and stimulate critical thinking. This study aims to examine the effectiveness of implementing the PBL-based NHT model in improving students’ interest and conceptual understanding of mathematics among tenth-grade students at MA Zainul Hasan Genggong. The research was conducted through Classroom Action Research, combining quantitative data (tests and questionnaires) and qualitative data (observations and interviews). The participants consisted of 21 students. The instruments included a learning interest questionnaire, multiple-choice tests to assess conceptual understanding, observation sheets, and interview guidelines. The results indicate an increase in the average learning interest score from 61% (moderate category) to 73% (high category), and an improvement in conceptual understanding from an average of 42.86% in Cycle I to 82.61% in Cycle II. The qualitative data supported these findings, showing students’ more active involvement in discussions and problem-solving activities. Therefore, the integration of the NHT–PBL model proved effective in enhancing students’ interest and conceptual understanding. These findings recommend strengthening problem-based cooperative learning designs by considering aspects such as time allocation, topic selection, and students’ ability heterogeneity.